A Magnified Adaptive Feature Pyramid Network for automatic microaneurysms detection. (December 2021) - Sun, Song; Cao, Zhicheng; Liao, Dingying; Lv, Ruichan
Abstract: Diabetic retinopathy (DR), as an important complication of diabetes, is the primary cause of blindness in adults. Automatic DR detection poses a challenge which is crucial for early DR screening. Currently, the vast majority of DR is diagnosed through fundus images, where the microaneurysm (MA) has been widely used as the most distinguishable marker. Research works on automatic DR detection have traditionally utilized manually designed operators, while a few recent researchers have explored deep learning techniques for this topic. But due to issues such as the extremely small size of microaneurysms, low resolution of fundus pictures, and insufficient imaging depth, the DR detection problem is quite challenging and remains unsolved. To address these issues, this research proposes a new deep learning model (Magnified Adaptive Feature Pyramid Network, MAFP-Net) for DR detection, which conducts super-resolution on low quality fundus images and integrates an improved feature pyramid structure while utilizing a standard two-stage detection network as the backbone. Our proposed detection model needs no pre-segmented patches to train the CNN network. When tested on the E-ophtha-MA dataset, the sensitivity value of our method reached as high as 83.5% at false positives per image (FPI) of 8 and the F1 value achieved 0.676, exceeding all those of the state-of-the-art algorithms as well as the human performance of experienced physicians. Similar results were achieved on another public dataset of IDRiD. Graphical abstract: Image 1 Highlights: A truly end-to-end deep-learning model for microaneurysms detection is introduced. Our method is especially designed for small-sized targets via image interpolation. An Adaptive Feature Pyramid Network is proposed for better feature representation. The method needs no pre-segmented patches during training. State-of-the-art performance is achieved in both FROC curves and F1 measure.